Tinjauan hukum eksekusi harta pailit debitor di luar negeri (Lex Jurnalica, 2020)
Compliance with the decision of the bankruptcy of the Indonesian Commercial Court against debtors who have assets abroad raises the problem of bankruptcy across borders. The problem lies in the authority of the Indonesian Commercial Court in executing the assets of debtors who are abroad. The rejection of the execution of foreign court decisions is closely related to the concept of state sovereignty. The Bankruptcy Law does not yet have clear legal rules for handling bankruptcy cases across national borders. The absence of specific provisions regarding how to resolve the bankruptcy decision declared by the Indonesian Commercial Court against the assets of bankrupt debtors in foreign countries raises a problem in terms of its execution. The importance of cross-border bankruptcy law should be considered to be regulated in the Bankruptcy Act in Indonesia so as not to cause confusion for law enforcement and the public regarding problems in cross-border bankruptcy.